Livestock Disease Vaccination in Rural Indonesia: A Study on Communication Strategies and Community Participation - Robi Agustiar; Agung Triatmojo; Ali Agus; Budi Guntoro (Faculty of Animal Science, Universitas Gadjah Mada, 2026)
This study investigates strategies to improve vaccination coverage for Foot-and-Mouth Disease (FMD) and Lumpy Skin Disease (LSD) in rural farming in Indonesia. Using a Participatory Rural Appraisal (PRA) approach, this qualitative study identifies effective communication strategies and technical solutions to enhance vaccination uptake and biosecurity practices. A total of 260 participants from five regions including Bali, East Nusa Tenggara, South Sulawesi, Yogyakarta, and Central Java participated in separate focus group discussions held in pairs among farmers, livestock traders, and government officials, focusing on farmers' perceptions, media habits, and information-seeking behaviors regarding disease prevention. Findings show that farmers supportive of vaccination access reliable information via agricultural extension workers and digital platforms, while skeptics rely on familiar, traditional sources. The study emphasizes the critical role of community leaders, such as religious figures and village heads, in disseminating trustworthy information. Technical recommendations include integrating vaccination with veterinary services, establishing compensation funds for livestock losses, and utilizing technology to improve adherence. The study advocates for multi-sector collaboration among local governments, veterinary associations, and community leaders to address resource shortages and ensure vaccination success. It also recommends prioritizing face-to-face interactions, informal approaches, and leveraging social media, local wisdom, and culture-based activities, particularly during social and religious events, to engage farmers, especially the younger demographic